Broiler Performance and Meat Quality in Response to Different Kinds and Levels of Bio-Organic Supplements - Jaya, Alex (JPAIR Multidisciplinary Research, 2019)
The study determined the production performance and meat quality of broilers using different kinds and levels of bio-organic supplements. Four hundred fifty broiler chicks were randomly distributed to fifteen dietary treatments. Five birds in each treatment were used for meat quality evaluation following a 3 x 5 factorial in Completely Randomized Design (CRD). No significant differences were observed in the production performance of broilers supplemented with different kinds of bio-organic fertilizers except average daily gain and final live weight. Broilers supplemented with higher levels of bio-organic supplements including antibiotic significantly affected the production performance except for average daily water intake and dressing percentage. Feed cost per kilogram of broiler produced, feed cost per average daily gain and return above feed, chicks and supplement costs were not significantly affected by the different kinds of bio-organic supplements but significantly affected by the different levels of bio-organic supplements. Meat quality was significantly affected by the different kinds of bioorganic supplements except for taste and overall acceptability but was not significantly affected by increasing the levels of bio-organic supplements including those broilers supplemented with antibiotics in the drinking water. Better production performance was observed on broilers supplemented with different kinds and levels of bio-organic supplements in the drinking water but did not affect the meat quality.
Keywords: Broiler; Production; Meat Quality; Bio-Organic Supplements; Performance Evaluation; Philippines